The Challenges of Inclusive Education in Ghana: A Literature Review - Mfoafo-M'Carthy, Magnus; Grischow, Jeff; Specht, Jacqueline; K. Mprah, Wisdom; Sider, Steve; Maich, Kimberly Anne; Must, Nicholas (Social Education Research, 2026)
This article presents a comprehensive review of peerreviewed scholarship on perceptions and knowledge of Inclusive Education (IE) in Ghana. Sixtyfive publications, released between 2007 and 2022, were identified through a systematic search of major academic databases and analyzed to map the evolution of IE research in the country. The studies were organized into two overarching thematic domains: (1) core focus areas-including attitudes toward IE, levels of knowledge among stakeholders, and the practical realities of implementation-and (2) policy-oriented recommendations. Across the literature, there is broad agreement that Ghana has established a solid legislative and policy foundation for IE. However, the transition from policy to practice remains uneven and slow, constrained by persistent gaps in resources, training, and public awareness. While the existing body of work offers rigorous and multidimensional examinations of IE, notable limitations remain. Research has disproportionately centered on teachers, with comparatively limited attention to other key stakeholders such as students, parents, school leaders, and community actors-though recent studies show a gradual shift toward more inclusive perspectives. Additionally, diachronic analyses are scarce, despite the long-term and evolving nature of IE implementation in Ghana. Overall, the reviewed studies illuminate the complexity of IE as both a policy agenda and a lived educational reality. The article concludes with targeted policy recommendations aimed at strengthening IE in Ghana, emphasizing the need for sustained professional development, improved resource allocation, and broader public engagement to reinforce inclusive education as a national priority.